Abnormal Papanicolau Smear and Colposcopic Findings, How Much They Correlate? - Abed, Dalal Oudah; Alnakash, Abdulrazak H. (Journal of Science in Medicine and Life, 2025)
Background: Cervical cancer is a significant health issue and a leading cause of death among women worldwide. However, the disease is preventable through early detection and appropriate treatment. Screening tests like Pap smear can identify early cervical epithelial changes, while colposcopy can detect invasive or preinvasive lesions for biopsy and further management. Implementing robust screening programs is crucial in preventing cervical cancer. Aim of the study: To estimate the accuracy of pap smear in the estimation of abnormal findings in comparison to colposcopy findings. Patients and methods: a cohort study conducted in the Department of Obstetrics and Gynecology at Al-Elwiya Maternity Teaching Hospital / Baghdad during a period from the 1st of June 2022 till the 1st of June 2023. The study included non-pregnant women who attend the gynecological clinic for a pap smear, and the results showed abnormal pap smear findings. All participants with abnormal pap smears underwent colposcopic examination. Comparison of the result of pap smear with colposcopy and with histopathology, and comparison of colposcopy results with histopathology results, to estimate and compare the accuracy of both pap smear and colposcopy. Results: the total cases were 117 case, 78 women had abnormal pap smear. Nulliparity, and secondary smoking were higher in cases of high-grade and cervical cancer cases. The accuracy of pap smear in detecting low-grade cervical interepithelial neoplasia was 82.1% with sensitivity and specificity of 92.1% and 72.5% respectively. With false positive rate of 6.4%. While the accuracy of colposcopy in the prediction of low-grade cervical interepithelial neoplasia (in comparison to histopathological test) was 91% with sensitivity and specificity of 91.9% and 90.2%. The predictive ability was much better using colposcopy (87.1% and 93.6% for sensitivity and specificity respectively). Conclusion: Pap smear results correlate with colposcopy and histopathological results with high sensitivity in detecting low and high grade cervical intraepithelial neoplasia.